The Effectiveness of Tooth Brushing Education on Reducing Plaque Index (Patient Hygiene Performance Index) in Mentally Retarded Children - Sukanti, Eka; Faisal, Muhammad; Zulfikri; Arnetty (POLTEKKES KEMENKES PADANG, 2023)
The main cause of caries and periodontal disease is plaque. Plaque can be removed by brushing your teeth. Children with mental disabilities or mental retardation have limitations in functioning themselves and adjusting to the environment. The prevalence of caries is 30% higher than normal children and poor oral hygiene is a problem faced by mentally retarded children. The purpose of this study was to analyze the effectiveness of tooth brushing education on reducing plaque index (Patient Hygiene Performance Index) in mentally retarded children at SLB N 02 Padang. The research design used was a Pre- Experimental One Group Pre and Posttest design with an initial plaque index examination (pretest) and a plaque index examination after brushing education (posttest), with a population of 86 people, the sampling technique was purposive sampling, obtained a sample of 45 person. The study was conducted at SLB N 02 Padang in 2019. The results showed a higher difference in the PHP index, namely for moderate mental retardation at 1.3 while the difference in numbers for mild mental retardation was 1.28. Data analysis using statistical tests with paired sample t-test showed that there was a significant difference between the PHP index before and after education about brushing teeth in children with mild and moderate mental retardation. It is recommended to respondents to always apply the brushing technique that has been given, and brush their teeth at least twice a day, ie in the morning after breakfast and at night before going to bed and guide the mentally retarded children one by one when brushing their teeth.